2017
DOI: 10.1016/j.jsams.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the performance characteristics of a winning outcome in elite mixed martial arts competition

Abstract: word count: 248Corresponding Author: Mr. Lachlan P. James, l.james1@uq.edu.au Conclusions:The decision tree analyses suggest that grappling activity and technique accuracy are of particular importance in achieving victory in elite-level MMA competition. The DFA results supported the importance of these performance indicators. Decision tree induction represents an intuitive and slightly more accurate approach to explaining bout outcome in this sport when compared to DFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 14 publications
7
65
2
4
Order By: Relevance
“…Absolute and relative peak strength were significantly higher for GM when compared to AO athletes, and is similar to that observed in other combat sports [16,33]. The importance of the summation of forces in rotational sports (e.g., the expression of lower-body force correlating to improved upper-body performance) has been demonstrated in elite handball [34] and baseball athletes [35,36], although limited research has been conducted in combat sports, particularly in international or national-level judokas.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Absolute and relative peak strength were significantly higher for GM when compared to AO athletes, and is similar to that observed in other combat sports [16,33]. The importance of the summation of forces in rotational sports (e.g., the expression of lower-body force correlating to improved upper-body performance) has been demonstrated in elite handball [34] and baseball athletes [35,36], although limited research has been conducted in combat sports, particularly in international or national-level judokas.…”
Section: Discussionsupporting
confidence: 86%
“…In combat sports, recent evidence has demonstrated that physical performance qualities contribute to success in Brazilian jiujitsu [14], taekwondo [10] and mixed martial arts [15]. In mixed martial arts for example, James et al [16] established that lower-body performance characteristics, particularly dynamic strength, were significantly greater in more successful compared to less successful athletes. To date, although there are a substantial number of studies which have examined the physical performance qualities underpinning successful competition performance in adult judokas [7], less evidence exists in juniors.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study might also have important implications for technical training. As many technical factors are dictated by velocity also, the findings of this investigation provide evidence that those who are stronger may more quickly respond to sports specific training.…”
Section: Perspectivementioning
confidence: 66%
“…MMA Fights are composed of three to five rounds lasting 5' with 1' intervals, where winning is achieved by knockout, technical knockout, submission or judge's decision [1][2] . The analysis and diagnosis of technicaltactical performance in MMA can be performed through videos, providing feedback to improve performance [2][3][4] , allowing the coach to develop a higher variety of strategies which interfere in the choice and the frequency of actions taken during combat [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…This information can be used in inferences about the intensity and energy demands used in combat 7 . In fact, when MMA athletes are consistently training at high intensity and there is no control of training load, their of injury risk increases [1][2][3][4][5][6][7][8][9][10][11] , affecting their competitive performance.…”
Section: Introductionmentioning
confidence: 99%